MEMBANGUN IDENTITAS BUDAYA BANYUMASAN MELALUI DIALEK NGAPAK DI MEDIA SOSIAL - Pawestri, Ananda Galuh (Jurnal Pendidikan Bahasa dan Sastra, 2019)
Ngapak dialect is a cultural identity from Banyumasan area which includes Banjarnegara, Purbalingga, Banyumas, Cilacap, and Kebumen regency. The Ngapak dialect has a unique pronunciation that is assertive (luged) and without a doubt (ampang). This research explains how the ngapak dialect was chosen as a symbol of the Banyumasan’s cultural identity to interacting on social media. This research uses a qualitative method with a virtual ethnographic approach and also supported by the constructivism paradigm. The data was collected by observation, interviews, and documentation as the primary data and literature studies as the secondary data. The results of this research are ngapak dialect is the development of the perceptions of the stereotypes with the ngapak dialect that exist and the dialect of ngapak itself. The perception of the Banyumasan cultural community regarding the Ngapak dialect is unique, cool, and rich so don't be embarrassed and should be proud because Ngapak dialect has potential. Banyumasan cultural community uses dialect ngapak as content with comedy themes. The reflection of the comedy itself is the character of the Banyumasan folks called cablaka and mbanyol. Cablaka means pure and mbayol means silly or funny.